Postmenopausal hyperandrogenism of ovarian origin: A clinicopathologic study of five cases - S Ajith; George Beena; Nitu Mariam Mathew; E K Omana (Wolters Kluwer Medknow Publications, 2016)
In postmenopausal women presenting with virilization and elevated testosterone levels, laparoscopic salpingo-oophorectomy should be considered after exclusion of adrenal causes. A clinicopathological study was conducted among those women who presented with features of hyperandrogenism in our postmenopausal clinic over a period of 2 years. Relevant past medical and surgical histories were elicited. Basic hormonal evaluation and radiological imaging were done. Laparoscopic bilateral salpingo-oophorectomy was done. Six weeks postoperatively, serum testosterone was undetectable with significant clinical improvement. There was no recurrence of symptoms during the follow-up period of 2 years. Treatment of postmenopausal women with hyperandrogenism and virilization with laparoscopic bilateral salpingo-oophorectomy is effective if she has no pronounced ovarian enlargement or adrenal tumor on imaging. An extensive endocrine testing and a detailed search for metastatic disease may be unnecessary.